If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 5 + -5x = 13 Reorder the terms: 5 + x + -5x = 13 Combine like terms: x + -5x = -4x 5 + -4x = 13 Solving 5 + -4x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -4x = 13 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 13 + -5 -4x = 13 + -5 Combine like terms: 13 + -5 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| 5x-23=5x-1 | | 2x^3+5x^2-x-6=0 | | -8x+2=-6 | | 3=x+5-4 | | y+-6x+-9=0 | | (3x^3-24)=0 | | 4(3+5w)=11 | | ln(x^2+3x+4)=0 | | -15+2(x)=-11 | | -15+2(5)= | | -2a+3-4=-1 | | -15+2(3)= | | x-3-1=2 | | 3m+2x=y | | 4 = b8 | | 4t+1=7t+10 | | 17-6x+4=3x+21-3x | | -13+12(x)=11 | | -8+14v=12v | | n+31+2n=17 | | 0=r-4+6 | | 13=u-6 | | -13+12(7)= | | 2(b+3)=14 | | 5p=-8+6p | | 18s-11s-5s=20 | | 4(7s+3)=-15 | | -194-7x=3x+66 | | 2h=1.5h(15*2) | | 54=6+6x | | -4n-4=-56 | | -3s=-135 |